Aplikasi Web Mobile Android Pada Wahaha Seafood Lampung Menggunakan Firebase Cloud Messaging (FCM) - Lutfi Pratama, Aldi; Kurniawan, Rio; Sulyono, Sulyono; Mutiara, Suci (Jurnal Informatika, 2026)
Abstract — Service quality and organizational effectiveness are highly influenced by employee performance. At Wahaha Seafood Lampung, the process of delivering information such as memos, work reminders, and performance evaluations is still conducted manually, resulting in delays in information dissemination, suboptimal employee coordination, and difficulties in monitoring employee performance in an integrated manner. These issues highlight the need for an information system capable of supporting internal communication and real-time employee performance evaluation. This study aims to design and develop a web-based and Android-based application for information dissemination, notification delivery, and employee performance evaluation using Firebase Cloud Messaging (FCM). The research employed an applied research approach with a system development methodology using the Waterfall model, which consists of requirements analysis, system design, implementation, testing, deployment, and maintenance stages. The system was developed using the Laravel framework for the web application, Flutter for the Android application, MySQL as the database management system, and Firebase Cloud Messaging (FCM) as the real-time notification service. The system provides features for memo distribution, work reminders, automated notifications, and weekly performance evaluations for Persons in Charge (PICs) and staff based on indicators including attitude, discipline, creativity, and communication. The testing results indicate that all system features functioned according to the specified requirements, including both manual and automated real-time notification delivery as well as proper management of performance evaluation data. Therefore, the developed system is capable of improving internal communication effectiveness, facilitating employee performance monitoring, and supporting increased organizational productivity in a more structured and integrated manner.   Key word — Performance, Android, Webservice, Firebase Cloud Messaging (FCM), Company, Evaluation System